Anti-inflammatory intestinal activity of Abarema cochliacarpos (Gomes) Barneby & Grimes in TNBS colitis model - da Silva, Maria Silene; Sanchez-Fidalgo, Susana; Talero, Elena; Cardeno, Ana; da Silva, Marcelo Aparecido; Vilegas, Wagner [UNESP]; Monteiro Souza Brito, Alba Regina; Alarcon de La Lastra, Catalina (Elsevier B.V., 2010)
Aim of the study To assess the anti-inflammatory effect of butanolic fraction of methanolic extract from bark of Abarema cochliacarpos in acute ulcerative colitis model induced by intracolonic administration of trinitrobenzene sulfonic acid (TNBS) in Wistar ratsMaterials and methods: Abarema cochliacarpos (100 and 150 mg/kg/day) was administered by gavage 48, 24 and 1 h prior to the induction of colitis with 10 mg/kg of TNBS and, 24 h laterResults: Phytochemical studies by mass spectrometry (MS) and nuclear magnetic resonance spectroscopy (NMR) revealed that catechins were a major component into condensate class of tannins Treatment with Abarema cochliacarpos decreased significantly macroscopic damage as compared with TNBS (p <0.05) Histological analysis showed that both doses of the extract improved the microscopic structure and preserved some areas of the colonic mucosa structure In addition, myeloperoxidase activity (MPO), as a marker of neutrophil infiltration, was decreased in a dose-dependent way (p < 0 01 and p < 0.001 respectively), TNF-alpha level was also diminished with the highest dose of the extract (p < 0 001) and, IL-10 level obtained no significant results In order to elucidate some of the mechanisms, expression of inducible inflammatory enzymes, such as cyclooxygenase (COX)-2 and nitric oxide synthase (iNOS), were studied showing a significant reduction Finally, the involvement of c-Jun N-terminal kinase (JNK) signalling demonstrated a reduction in the JNK activation with the highest dose (p < 005 vs TNBS)Conclusions We have shown for the first time that the extracts obtained from Abarema cochliacarpos bark possess active substances, which exert marked protective effects in acute experimental colitis, confirming and justifying. at least in part, the popular use of this plant to treat gastrointestinal diseases (C) 2010 Elsevier B.V. All rights reserved
Keywords: Abarema cochliacarpos (Mimosaceae); Colitis; Neutrophils; Cytokines; Inducible nitric oxide synthase; Cyclooxygenase; c-Jun N-terminal kinase